Party political chaplaincy? – Methodist ministry to political parties - Ndikho Mtshiselwa; Simphiwe S. Mthembu (HTS Teologiese Studies/Theological Studies, 2018)
The debate on church and party politics is far from being exhausted in South Africa. Although the Methodist Church of Southern Africa discourages the participation of clergy persons in political parties, it is becoming critical that the church offers a prophetic voice in the political sphere. Issues of morality and spirituality within the political parties necessitate a careful involvement of the Church in politics. This article therefore sets out to offer a theological reflection on the (possible) ministry of Methodist clergy persons to political parties in South Africa.